Immunotherapy in gastrointestinal cancers - Grierson, Patrick; Lim, Kian-Huat; Amin, Manik (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
Gastrointestinal (GI) cancers such as gastric, esophageal, pancreas, hepatobiliary, colorectal and anal cancers are a major cause of cancer related mortality worldwide. Traditional treatment options such as chemotherapy, surgery, radiation therapy, monoclonal antibodies and anti-angiogenic agents have been the backbone of treatment of GI cancers in various stages. Current cancer research is moving forward to incorporate immunotherapies in the treatment of GI cancers either as single agent or in combination with current available treatment modalities. This review summarizes the existing and ongoing immunotherapies in the treatment of GI cancers.